Anti-Vibrio Indole-Diterpenoids and C-25 Epimeric Steroids From the Marine-Derived Fungus Penicillium janthinellum - Guo, Xing-Chen; Xu, Lan-Lan; Yang, Rui-Yun; Yang, Meng-Yue; Hu, Lian-Dong; Zhu, Hua-Jie; Cao, Fei (Frontiers in Chemistry, 2019)
Two new indole-diterpenoids, penijanthines C and D (1 and 2), and a pair of new steroidal epimers, penijanthoids A and B (5 and 6), along with two known indole-diterpenoids (3 and 4), were obtained from the marine-derived fungus Penicillium janthinellum. The absolute configuration of 1 was assigned by calculated ECD method. The Snatzke′s method was used to determine the absolute configuration of C-26 for 1. The absolute configuration of 3 was established by X-ray diffraction and calculated ECD methods for the first time. DP4 plus approach was applied to elucidate the absolute configurations of 5 and 6. Compounds 5 and 6 represent the first examples of steroids forming a five-membered lactone between C-23 and C-27 from marine fungi. Compounds 1, 2, 5, and 6 showed anti-Vibrio activity against pathogenic Vibrio spp. with MIC values ranging from 3.1 to 50.0 μM.